2007
DOI: 10.1210/en.2007-0066
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleotides Block Bone Mineralization in Vitro: Evidence for Dual Inhibitory Mechanisms Involving Both P2Y2 Receptors and Pyrophosphate

Abstract: Extracellular nucleotides, signaling through P2 receptors, may act as local regulators of bone cell function. We investigated the effects of nucleotide agonists [ATP, ADP, uridine triphosphate (UTP), and uridine diphosphate] and pyrophosphate (PPi, a key physiological inhibitor of mineralization) on the deposition and mineralization of collagenous matrix by primary osteoblasts derived from rat calvariae. Our results show that extracellular ATP, UTP, and PPi strongly and selectively blocked the mineralization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
165
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 125 publications
(187 citation statements)
references
References 31 publications
18
165
4
Order By: Relevance
“…Initial functional studies showed that low micromolar concentrations of ATP and UTP acting via P2Y 2 receptors inhibited bone formation by cultured rat osteoblasts [11,202]. A follow-up investigation demonstrated that ATP and UTP selectively inhibited the mineralisation of the organic matrix and provided further evidence for involvement of the P2Y 2 receptor subtype [203]. Subsequent skeletal analysis of P2Y 2 receptor knockout mice by dual energy X-ray absorptiometry (DEXA) and microcomputed tomography (μCT) demonstrated large increases in trabecular and cortical bone parameters in the long bones [117,204].…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial functional studies showed that low micromolar concentrations of ATP and UTP acting via P2Y 2 receptors inhibited bone formation by cultured rat osteoblasts [11,202]. A follow-up investigation demonstrated that ATP and UTP selectively inhibited the mineralisation of the organic matrix and provided further evidence for involvement of the P2Y 2 receptor subtype [203]. Subsequent skeletal analysis of P2Y 2 receptor knockout mice by dual energy X-ray absorptiometry (DEXA) and microcomputed tomography (μCT) demonstrated large increases in trabecular and cortical bone parameters in the long bones [117,204].…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%
“…Expression of multiple NTPdases and NPPs by osteoblasts has now been reported [203,204]. Of these, NPP1 has emerged as having a particularly important role in bone.…”
Section: Atp Hydrolysis and The Effects On Bone Mineralisationmentioning
confidence: 99%
See 1 more Smart Citation
“…This release has been reported to be increased by mechanical stress and is known to have a paracrine or autocrine effect on osteoblasts and osteoclasts partly via activation of specific P2 receptors. However, this ATP is also known to be rapidly metabolised to adenosine (which can then act via its own receptors) by the sequential actions of a number of enzymes, including ecto-nucleotide pyrophosphatase/phosphodiesterase-1 (ENPP1), CD73 and alkaline phosphatases [4,17]. Interestingly, a mouse model lacking ENPP1 has recently been shown to have a severe disruption to the architecture and mineralization of longbones [18].…”
Section: Commentarymentioning
confidence: 99%
“…Osteoblasts, the bone-forming cells, express multiple P2 receptors [5,6], in a differentiationdependent manner [7,8], and respond to extracellular nucleotides with a prompt increase in intracellular calcium [7][8][9][10]. Importantly, exogenous ATP, UTP and other nucleotide analogues also potently inhibit mineralisation of bone formed by osteoblasts in culture [8,11,12]. Moreover, endogenous ATP released by osteoblasts also appears to act as a significant local inhibitor of mineralisation [13].…”
Section: Introductionmentioning
confidence: 99%